Next‐generation sequencing confirms the implication of SLC24A1 in autosomal‐recessive congenital stationary night blindness. Issue 6 (4th March 2016) - Neuillé, M.; Malaichamy, S.; Vadalà, M.; Michiels, C.; Condroyer, C.; Sachidanandam, R.; Srilekha, S.; Arokiasamy, T.; Letexier, M.; Démontant, V.; Sahel, J.‐A.; Sen, P.; et al.
Abstract : Congenital stationary night blindness (CSNB) is a clinically and genetically heterogeneous retinal disorder which represents rod photoreceptor dysfunction or signal transmission defect from photoreceptors to adjacent bipolar cells. Patients displaying photoreceptor dysfunction show a Riggs‐electroretinogram (ERG) while patients with a signal transmission defect show a Schubert–Bornschein ERG. The latter group is subdivided into complete or incomplete (ic) CSNB. Only few CSNB cases with Riggs‐ERG and only one family with a disease‐causing variant in SLC24A1 have been reported. Whole‐exome sequencing (WES) in a previously diagnosed icCSNB patient identified a homozygous nonsense variant in SLC24A1 . Indeed, re‐investigation of the clinical data corrected the diagnosis to Riggs‐form of CSNB. Targeted next‐generation sequencing (NGS) identified compound heterozygous deletions and a homozygous missense variant in SLC24A1 in two other patients, respectively. ERG abnormalities varied in these three cases but all patients had normal visual acuity, no myopia or nystagmus, unlike in Schubert–Bornschein‐type of CSNB. This confirms that SLC24A1 defects lead to CSNB and outlines phenotype/genotype correlations in CSNB subtypes. In case of unclear clinical characteristics, NGS techniques are helpful to clarify the diagnosis. Abstract :